Life Cycle Assessment of Hemodialysis Treatments. - Magrogan, Danielle. (2017)
Abstract: Close to 400,000 people in the US suffer from end stage renal disease and require regular HD treatments as a life sustaining therapy. HD consumes high amounts of energy, water, and disposables, but the environmental impacts of the treatment has only begun to be characterized in the literature. A life cycle assessment (LCA) methodology is used to determine the impacts of HD treatments in the scenarios where: * dialyzers are used once and then thrown away. * dialyzers are reused, reprocessed between uses, and then thrown away after about 20 uses. * dialyzers are recycled by recovering materials from the dialyzer cartridge housing. Environmental impacts are calculated across the nine impact categories in the TRACI2 LCIA method. This study demonstrates that reusing and recycling dialyzers creates substantial reductions in the life cycle impacts of individual dialyzers, but offers only modest benefits when put in context of the entire HD treatment.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Civil Engineering.; Advisor: Stephen Levine.; Committee: Daniel Weiner, and Thomas Gloria.; Keywords: Environmental engineering, Sustainability, and Health sciences.